Production methods of ceramic-reinforced Al-Li matrix composites: A review - Zhang, Kaiqiang; Won Jang, Ho; Van Le, Quyet (Journal of Composites and Compounds, 2020)
Recently, the increasing need for good quality, high performance, and low-cost materials has directed research to composite materials rather than monolithic materials. In the case of metal matrix composites (MMCs), composites based on aluminum matrix have been widely developed for the automobile and aerospace industry as well as structural applications due to having a low cost, high wear resistance, and high strength to weight ratio. Moreover, a facile and economical method for the production of the composites is a very important factor for expanding their application. Ceramic reinforcements such as graphite, silicon carbide, alumina, and fly ash particulates can be introduced in metal matrices. Moreover, there has been considerable interest in developing Al-Li alloys and composites because of having high specific strength and high specific modulus. The present article has focused on the development of aluminum-lithium alloy composites as well as their production methods.